Study of Phytochemical, Antioxidant and Antimicrobial Activity of Artocarpus heterophyllus - Thapa, Nita; Thapa, Pratiksha; Bhandari, Jaya; Niraula, Prasodhan; Shrestha, Nikita; Shrestha, Bhupal G (Nepal Journal of Biotechnology, 2016)
In today’s world, search for natural medicines is increasing as a result of drug resistance of pathogens and also due to negative consequences of antibiotic. Presence of phytochemicals, antioxidant potential and antimicrobial activity of Artocarpus heterophyllus was carried out in this study. Leaf of this plant was subjected to warm extraction with three different solvents namely methanol, aqueous methanol and ethyl acetate. Leaf extract showed the presence of coumarin, alkaloid, terpenoid in methanol solvent; tannin, coumarin, saponin in aqueous methanol extract and coumarin, terpenoids in ethyl acetate solvent. Further, antimicrobial activity was assessed through disc diffusion method with six pathological bacteria and two fungi strains in four different concentrations of plant extract. Largest ZOI of 16mm was obtained against B. subtilis in 200mg/ml concentration for ethyl acetate extract. Antioxidant potential was measured by DPPH (Diphenyl-2-picrylhydrazyl) assay. DPPH free radical Scavenging Activity was expressed in % inhibition with L Ascorbic acid as standard and leaf extract in methanol showed the best activity.